THE EFFECTIVENESS OF CLOUD ACCOUNTING IN MAKING FINANCIAL DECISION FOR CAPITAL INVESTMENT COMPANIES AL-KHAIR FINANCIAL INVESTMENT COMPANY MODEL - Aqeel salim Mohammad; Zainab Faiq Mohammed; Hanaa Qasim Mathboob (Scholar Express Journals, 2024)
The ongoing revolution in information technology has greatly affected the information system and financial and accounting decision-making more effectively and efficiently than before. The implementation of various activities that have been implemented manually has become electronic. As a result of all this, a new term for accounting has emerged, which is "cloud accounting", a term that means how to access the accounting information system Accessing the internet without requiring prior installation of accounting software on individual computers or servers within the network., as well as benefiting from it in financial decision-making magazines that have a significant role in the employment of money companies, which are increasingly being used.
Keywords: cloud accounting; IT; financial decisions